PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SDN 29 PEKANBARU - Yola Charatula Aulia; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is done because there are still many students of class IV SDN 29 Pekanbaru which can not be in search of narrative essay, which can be seen from writing data of narrative essay, from 36 students of grade IV which get very high category no (0%), 2 students (5.56%), moderate category as many as 8 students (22.22%) and less language category as many as 26 students (72.22%). The type of research used is classroom action research (PTK). Each cycle consists of two meetings and one daily test. This research was conducted at SDN 29 Pekanbaru class IV A with 36 students consisting of 21 male students and 15 female students. The purpose of this research is to improve the skill of writing the narrative essay of fourth graders of SDN 29 Pekanbaru by applying cooperative learning model with serial drawing media. Research result. This can be seen from the burden of writing narrative essay on the basic score of students before applied cooperative learning model with the image series 57,13 increase in the cycle of Iitung 33.52% to 76.28. In the second cycle also increased by 40.96%. to 80,53 Activity of teacher at first meeting of cycle I the percentage of 75% with enough category then increase at second meeting of cycle II to 95,83% with very good category. Student activity at first meeting of cycle I of percentage 66,66% with enough category then at second meeting second cycle become 91,66% with very good category.Key Words: cooperative, series picture media, narration writing skills